The Positive Impact Of Virtual Class-Based On Calculus II Teaching Materials In Improving The Conceptual Understanding Of Informatics Engineering Students - Tesi Anggraini; Wardani Rahayu; Makmuri Makmuri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
This research aims to analyze the validity of Calculus II teaching materials based on virtual classes; the effectiveness of teaching materials that have been designed towards improving students’ understanding of mathematical concepts. The method used in this research is ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The research subjects were students of Informatics Engineering UNINDRA 4th semester who took Calculus II courses consisting 2 (two) classes, namely the experimental class consisting of 14 students and 15 students of the control class. Instruments and data collection techniques used in the form of observation, tests, and questionnaires. Data analysis used independent sample test and normalized gain score. The result showed that Calculus II teaching materials were based on virtual class was valid and effective to improve students’ understanding of concepts so it can be concluded that the teaching materials for Calculus II based on virtual classes are valid and suitable for use in learning and are effective and practical to improve student’s conceptual understanding.